New Advances in Vehicular Technology and Automotive Engineering - Paulo Carmo, Joao; Eduardo Ribeiro, Joao (IntechOpen, 2012)
An automobile was seen as a simple accessory of luxury in the early years of the past century. However, in the present days it's undeniable the amount of technology and human effort applied by the vehicular industry for developing high?quality vehicles, but still, cheap for the common person. In this context, this book tries not only to fill a gap by presenting new and updated subjects related to the vehicular technology and to the automotive engineering but also to provide guidelines for future research. This book is a result of many valuable contributions from worldwide experts of automotive's field. The amount and type of contributions were judiciously selected to cover as possible the widest range of research. The most recent and cutting?edge subjects can be found in this book, e.g., electronics, mechanics, materials, and manufacturing.